1990
DOI: 10.1139/v90-017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lignin residues derived from the alkaline hydrolysis of glycol lignin

Abstract: . 68, 82 (1990).Lignin residues from the alkaline hydrolysis of solvolytic lignin have been characterized by elemental analysis, size exclusion chromatography, Fourier transform infrared spectroscopy, I 3 c NMR, and for methoxyl content. All lignin residues were found to have higher carbon and lower oxygen contents than the original glycol lignin. Methoxyl contents decreased with increasing severity of treatment. All treated lignins have lower molecular weights than the original, which is indicative of the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…It can be observed that the prominent difference was 3407 cm −1 (O-H stretching in hydroxyl group), 2917 cm −1 (C-H stretching in methyl and methyene groups), 1645 cm −1 (C O stretching in conjugated aryl ketone), 1247-1519 cm −1 (guaiacyl and syringyl lignin characteristic peaks), and 1031 cm −1 (aromatic C-H in-plane deformation). 21,22 All these bands disappeared or decreased after alkali pretreatment assisted by photocatalysis. These results again highlight the delignification effect of this pretreatment process.…”
Section: Physical Properties and Microstructure Of Pretreated Rice Strawmentioning
confidence: 97%
“…It can be observed that the prominent difference was 3407 cm −1 (O-H stretching in hydroxyl group), 2917 cm −1 (C-H stretching in methyl and methyene groups), 1645 cm −1 (C O stretching in conjugated aryl ketone), 1247-1519 cm −1 (guaiacyl and syringyl lignin characteristic peaks), and 1031 cm −1 (aromatic C-H in-plane deformation). 21,22 All these bands disappeared or decreased after alkali pretreatment assisted by photocatalysis. These results again highlight the delignification effect of this pretreatment process.…”
Section: Physical Properties and Microstructure Of Pretreated Rice Strawmentioning
confidence: 97%
“…The methyl acetate may be one of the impurities in the ethylene glycol, while the various 1,3 dioxolane derivatives are produced from the ethylene glycol. The other identified compounds derive from glucose pyrolysis as shown by Niemela (1988a and1988b).…”
Section: The S Fraction (Condenser Trap At 0°c)mentioning
confidence: 99%
“…
It is well known that, as a result of thermo-chemical treatment in a water-alkaline medium, lignin is destroyed and low-molecular-weight phenol compounds are obtained [1][2][3][4]. Low-molecular-weight phenol compounds (LMPC) 2-methoxyphenol, 2,6-dimethoxyphenol, vanillin, etc.
…”
mentioning
confidence: 99%